Isolation and identification of Candida albicans to produce in house helicase for PCR - B. P. Haw; B. Venugopal; O. Eugene; I. Asma; S. Sasidharan (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Candida albicans is a dimorphic fungus that can grow in a wide range of temperature. In such case, this microorganism has the potential to produce enzymes that able to function at elevated temperature. These enzymes are also essential in the field of molecular biology and recombinant technologies. Therefore, the enzymes produced by Candida albicans could be applied in the polymerase chain reaction (PCR). The PCR is the most widely used in DNA amplification. In this study, Candida spp. were successfully isolated and collected from Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan, Malaysia. Different culture media were used to identify the morphology of colony. Based on the colonies growth on chromogenic agar, Candida sp. was identified. Microscopic examination (light and scanning microscopy) was carried out to identify the morphology of the isolate. A presumptive identification of germ tube test was performed to find out the dimorphic and pathogenicity characteristic of isolate. The formation of germ tubes from the isolate showed positive result of Candida albicans. A commercial Analytical Profile Index (API) Candida identification kit was used in this study as a phenotypic identification of Candida sp. The result of API Candida was confirmed that the isolate was the Candida albicans. Candida albicans was successfully isolated and identified phenotypically in this study for future in house helicase production.